Matka głupich? Filozoficzne aspekty nadziei - Witold Starnawski (Nicolaus Copernicus University in Toruń, 2009)
This text focuses on the problem of hope in a philosophical aspect. It has been based on the thought of st. Thomas, Roman Ingarden, Karol, Wojtyła, and particularly Gabriel Marcel. The author concentrates on two questions: 1. Are there any criteria to distinguish between two forms of hope: the first - that reveals reality, second - that deludes. 2. Can the experience of men in terms of natural, philosophical categories lead us to discovering and understanding hope? "To be future in the present" - is the existential position of hope.    It ought to be based on reality, not on desires or dreams. Hope means: no situation of evil or fear is ultimate. It is not the prediction of the future. Transcendental acts of men are philosophical basis of hope (Marcel, Wojtyła); they oppose everything, that passes away, ultimately - they oppose death.